Proprioceptive ability of fencing and table tennis practitioners - Bankosz, Z.; Szumielewicz, P. (Human Movement, 2014)
Purpose. The aim of the study was to compare the spatial component of proprioceptive ability by reproducing a upper limb movement typical in table tennis and fencing. Methods. The research comprised 41 young males of which 12 were table tennis players, 14 fencers, and 15 not involved in any competitive sports as a control. The experiment was based on assessing the precision of pronation and supination of the forearm at the elbow joint in recreating a set movement range by use of a goniometer. Results and conclusions. The results point to a higher level of proprioceptive ability in fencers and table tennis players than the control group but only in respect to the tasks executed with the dominant limb. This is inferred to be the result from the specific character of both sports (i.e. the intensive use of one limb and the consequent laterality of that limb) causing higher sensitivity and proprioception. This may provide a link between swordplay, table tennis, and the level of proprioception. The research methodology used herein may be useful in monitoring fencing training. Although not unequivocally statistically significant, the results indicate the potential for further research in this area.